Painless recurrent orbital wall infarction secondary to sickle cell disease: A case report - Lujain Alqurashi; Omar Rozy; Somaya Hanafi; Randa Khafaji (American Journal of Ophthalmology Case Reports)
Purpose: Describe the various presentations of the rare entity of orbital wall infarction secondary to sickle cell disease and highlight the importance of magnetic resonance imaging in differentiating the entity from other similar diagnoses. Observation: A 4-year-old child presented to the hospital with bilateral recurrent painless orbital wall infarction secondary to sickle cell disease. Orbital wall infarctions have been described before in the literature; However, the painless and recurrent nature is intriguing. Conclusion: Orbital wall infarctions secondary to sickle cell disease represent an unusual presentation of the disease and often pose a diagnostic dilemma. When considering differentiating orbital wall infarctions from other resembling entities, magnetic resonance imaging is considered superior to computed tomography due to its ability to delineate the ischemic changes in the bone marrow, which further aids in the diagnosis. In situations where the orbital wall infarction does not lead to orbital compression syndrome, a conservative approach should suffice.